2020
DOI: 10.1007/s12253-020-00797-0
|View full text |Cite
|
Sign up to set email alerts
|

The Function of NM23-H1/NME1 and Its Homologs in Major Processes Linked to Metastasis

Abstract: Metastasis suppressor genes (MSGs) inhibit different biological processes during metastatic progression without globally influencing development of the primary tumor. The first MSG, NM23 (non-metastatic clone 23, isoform H1) or now called NME1 (stands for nonmetastatic) was identified some decades ago. Since then, ten human NM23 paralogs forming two groups have been discovered. Group I NM23 genes encode enzymes with evolutionarily highly conserved nucleoside diphosphate kinase (NDPK) activity. In this review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 120 publications
0
26
0
Order By: Relevance
“…In this way, NME1 overexpressing cells treated with granzyme A are more sensitive to DNA damage [163,164]. In C. elegans and in humans NME promotes the engulfment of apoptotic cells through its interaction with Dynamin1 and 2 [103,165,166]. In the same study, this function was also seen in murine models where NME1 silenced bone marrow-derived macrophages cleared fewer apoptotic thymocytes [166].…”
Section: Nme Histidine Phosphorylation Signaling In Tumor Metastasis mentioning
confidence: 67%
See 3 more Smart Citations
“…In this way, NME1 overexpressing cells treated with granzyme A are more sensitive to DNA damage [163,164]. In C. elegans and in humans NME promotes the engulfment of apoptotic cells through its interaction with Dynamin1 and 2 [103,165,166]. In the same study, this function was also seen in murine models where NME1 silenced bone marrow-derived macrophages cleared fewer apoptotic thymocytes [166].…”
Section: Nme Histidine Phosphorylation Signaling In Tumor Metastasis mentioning
confidence: 67%
“…Surprisingly, unlike in humans, NDK-1 activates the Ras/MAPK signaling pathway [54,153]. A possible explanation of this difference is the differential regulation of the KSR scaffold [103]. Nevertheless, these data suggest that NME1 regulates Ras/MAPK signaling through its protein kinase function.…”
Section: Nme Histidine Phosphorylation Signaling In Tumor Metastasis mentioning
confidence: 76%
See 2 more Smart Citations
“…It has been shown that the endocytic function of Awd and its human and C. elegans homologues is involved in the motility of migrating cells. A dosage-dependent effect of Awd/NDK-1 (Nucleoside Diphosphate Kinase-1) has been reported on the migration of tracheal and border cells in Drosophila and of distal tip cells in C. elegans [ 13 ]. Furthermore, a role in the maintenance of genomic stability has also been assigned to both NME1 and Awd [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%